Halogen-free flame-retardant PC / ABS composition with high heat resistance and high impact resistance as well as preparation method and application thereof

The PC/ABS composition prepared through specific formulas and twin screw extrusion processes solves the problem of poor fluidity of existing materials, achieves comprehensive performance of high impact resistance, high heat resistance and halogen-free flame retardancy, and meets the material needs of thin-walled and miniaturized consumer electronics and smart equipment.

CN119875339APending Publication Date: 2025-04-25CHINA PETROLEUM & CHEMICAL CORP
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311378317.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-24
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The existing halogen-free flame-retardant PC/ABS alloy materials improve impact and heat resistance while improving their impact resistance and heat resistance, have poor fluidity and are difficult to meet the material needs of thin-walled and miniaturized consumer electronics and smart equipment.

Method used

The PC/ABS composition is prepared using a specific formula, which contains 60 to 80 parts of PC resin, 20 to 40 parts of ABS resin, 10 to 18 parts of flame retardant, 0.5 to 6 parts of synergistic flame retardant, 5 to 8 parts of impact modifier, 0.5 to 2 parts of compatibility agent, 0.2 to 0.6 parts of drip agent and 0.2 to 0.5 parts of antioxidant. It is extruded, cooled and granulated by a twin screw extruder.

Benefits of technology

It achieves comprehensive performance of high impact resistance, high heat resistance, high flowability and halogen-free flame retardancy, meets the material needs of thin-walled and miniaturized consumer electronics and smart equipment, and has a simple preparation process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004508650520000101
    Figure BDA0004508650520000101
Patent Text Reader

Abstract

The invention discloses a PC / ABS (Polycarbonate / Acrylonitrile Butadiene Styrene) composition, which is prepared from the following components in parts by weight: 60 to 80 parts of PC resin and 20 to 40 parts of ABS resin, relative to the total amount of 100 parts of PC resin and ABS resin, the PC / ABS alloy further comprises 10-18 parts of a flame retardant, 0.5-6 parts of a synergistic flame retardant, 5-8 parts of an impact modifier, 0.5-2 parts of a compatilizer, 0.2-0.6 part of an anti-dripping agent and 0.2-0.5 part of an antioxidant; wherein the flame retardant is a phosphate flame retardant, and the synergistic flame retardant is a potassium perfluorobutanesulfonate-free halogen-free environment-friendly flame-retardant master batch taking polycarbonate as a carrier. According to the PC / ABS composition disclosed by the invention, under the condition of ensuring that the flame retardant grade reaches UL94V-0 (1.6 mm), the mechanical property and the heat resistance of a product are not lost, and the PC / ABS composition is good in processability and suitable for preparing thin-walled and miniaturized consumer electronics, intelligent equipment and other workpieces.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of PC / ABS alloy materials, and particularly relates to a high-heat-resistant and high-impact halogen-free flame-retardant PC / ABS composition and a preparation method thereof. Background Art

[0002] PC / ABS alloy combines the excellent properties of PC and ABS, and is widely used in the automotive parts, mobile phones, home appliances and other industries, with an increasing market share. At present, phosphate-type flame retardants are mostly used to prepare halogen-free flame-retardant PC / ABS alloy materials on the market. However, phosphate-type flame retardants have a plasticizing effect, which will cause the impact resistance and heat resistance of the material to decrease a lot, thereby limiting the application of alloy materials. With the advent of the 5G era, the data transmission speed has greatly increased, and office, home appliances, and communication shells have higher requirements for flame retardancy and heat resistance. Therefore, there will be a great market demand for the development of halogen-free flame-retardant PC / ABS alloys with good fluidity, high heat resistance and high impact resistance for office equipment shells and smart home appliance shells.

[0003] Chinese patent CN112080123A discloses a high-flow, high-impact, high-temperature-resistant PC / ABS material and its preparation method, which mainly comprises the following components: 60-65 parts by weight of PC resin, 10-12 parts by weight of ABS resin, 2-4 parts by weight of compatible plasticizer, 0.2-0.4 parts by weight of antioxidant, 0.1-0.3 parts by weight of lubricant and 1-2 parts by weight of organic phosphorus flame retardant. This material can meet the market demand for large-scale thin-walled products made of PC / ABS alloy, but the flame retardant performance index is not high.

[0004] Chinese patent CN106905683A discloses a high impact heat-resistant halogen-free flame retardant PC / ABS alloy material and its preparation method, which mainly comprises the following components: 67% to 86% recycled PC resin, 4% to 19% recycled ABS resin, 1% to 6% AS resin, 0.5% to 5% compatibilizer, 3% to 10% toughening agent, 0.1% to 4.5% composite halogen-free flame retardant, 0.1% to 0.5% antioxidant, 0.1% to 1% lubricant, 0.1% to 1% anti-drip agent and 1% to 5% other additives. The material uses one or more of potassium perfluorobutyl sulfonate, potassium benzenesulfonylbenzenesulfonate, polydimethylsiloxane and polyorganosiliconesquioxane as halogen-free flame retardant, and the matrix resin material is recycled material, more other additives are added in the synthesis, the process is complicated, and it is not easy to realize industrial production.

[0005] Therefore, how to provide a halogen-free flame-retardant PC / ABS material with good fluidity, high heat resistance and high impact resistance to meet the market demand for thin-walled and miniaturized consumer electronics and smart equipment parts is a technical problem that needs to be solved at present. Summary of the invention

[0006] The present invention overcomes the shortcomings of the above-mentioned prior art and provides a high-heat-resistant and high-impact halogen-free flame-retardant PC / ABS composition and a preparation method and application thereof. The PC / ABS composition prepared by the present invention using a specific formula has high impact resistance, high heat resistance, high fluidity and halogen-free flame retardancy, excellent comprehensive performance, and a simple preparation process. It can meet the material requirements of thin-walled and miniaturized consumer electronics and intelligent equipment parts on the market, and has achieved unexpected technical effects.

[0007] The first aspect of the present invention is to provide a PC / ABS composition, which contains 60 to 80 parts of PC resin and 20 to 40 parts of ABS resin in parts by weight;

[0008] Relative to 100 parts of the total amount of PC resin and ABS resin, the PC / ABS composition further contains:

[0009] Flame retardant 10-18 parts,

[0010] Synergistic flame retardant 0.5-6 parts,

[0011] 5-8 parts of impact modifier,

[0012] Compatibilizer 0.5-2 parts,

[0013] 0.2-0.6 parts of anti-dripping agent,

[0014] 0.2-0.5 parts of antioxidant;

[0015] The flame retardant is a phosphate flame retardant, and the synergistic flame retardant is a halogen-free, environmentally friendly flame retardant masterbatch containing no potassium perfluorobutyl sulfonate and polycarbonate as a carrier.

[0016] According to the present invention, the synergistic flame retardant is a halogen-free, environmentally friendly flame retardant masterbatch without potassium perfluorobutyl sulfonate and with polycarbonate as a carrier. In a preferred embodiment of the present invention, the synergistic flame retardant contains polycarbonate, UASIC silsesquioxane flame retardant, Wacker silicon dispersant AK50 and antioxidant, for example, the synergistic flame retardant purchased from Quansheng Polycarbon Technology Co., Ltd. recorded in the embodiment of the present invention. The present invention selects environmentally friendly and efficient flame retardant masterbatch as the synergistic flame retardant, which can meet the requirements of good compatibility with other parts and uniform distribution of components during the extrusion process; it can also reduce or inhibit the loss of mechanical properties and heat resistance of alloy materials caused by phosphate flame retardants, especially the effect on heat deformation temperature.

[0017] In the present invention, PC resin refers to polycarbonate.

[0018] According to the present invention, the melt mass flow rate (i.e., melt index) of the PC resin can be selected within a wide range. In a preferred embodiment of the present invention, under the test conditions of a temperature of 300° C. and a load of 1.2 kg, the melt mass flow rate of the PC resin is 7 to 17 g / 10 min, for example, a melt index of 7 g / 10 min, a melt index of 12 g / 10 min, a melt index of 17 g / 10 min, and any two values ​​or any interval between any two values, preferably 11 to 13 g / 10 min.

[0019] In the present invention, ABS resin refers to acrylonitrile-butadiene-styrene copolymer.

[0020] According to the present invention, the rubber content in the ABS resin can be selected within a wide range. In a preferred embodiment of the present invention, based on the total weight of the ABS resin as 100wt%, the rubber content in the ABS resin is 11-13wt%, preferably 12.5-13wt%.

[0021] In a preferred embodiment of the present invention, the impact modifier is a methyl methacrylate-butadiene-styrene terpolymer and / or a silicon-based core-shell copolymer; preferably,

[0022] The model of the methyl methacrylate-butadiene-styrene terpolymer is M-722, and / or the model of the silicon-based core-shell copolymer is S2030.

[0023] In a preferred embodiment of the present invention, the flame retardant is at least one of triphenyl phosphate, bisphenol A bis(diphenyl) phosphate, and hydroquinone bis(diphenyl phosphate).

[0024] In a preferred embodiment of the present invention, the compatibilizer is a non-crystalline copolymer of methyl acrylate, preferably SAG-002 (preferably purchased from Jiayirong Polymer (Shanghai) Co., Ltd.).

[0025] In a preferred embodiment of the present invention, the anti-dripping agent is a copolymer of polytetrafluoroethylene, preferably K-PT201 (preferably purchased from QuanSheng Polycarbon Technology Co., Ltd.).

[0026] In a preferred embodiment of the present invention, the antioxidant contains a hindered phenol antioxidant and a phosphite, and preferably the mass ratio of the hindered phenol antioxidant to the phosphite is 1:(0.5-1.5).

[0027] In a preferred embodiment of the present invention, the PC / ABS composition contains 65-75 parts of PC resin and 25-35 parts of ABS resin, by weight.

[0028] In a preferred embodiment of the present invention, the PC / ABS composition contains, by weight, 12 to 15 parts of flame retardant, 2 to 3 parts of synergistic flame retardant, 6 to 7 parts of impact modifier, 0.8 to 1 part of compatibilizer, 0.2 to 0.4 part of anti-drip agent, and 0.3 to 0.4 part of antioxidant, relative to 100 parts of the total amount of PC resin and ABS resin.

[0029] According to the present invention, the PC / ABS composition can achieve at least one of the following indicators:

[0030] According to the UL94 vertical burning test standard, the UL94 (1.6 mm) of the PC / ABS composition reaches the V0 level;

[0031] Tested according to ISO 1133-1:2011 method A, temperature 260°C, load 5Kg, melt mass flow rate (260°C, 5kg) ≥ 30g / 10min, preferably above 34g / 10min, more preferably 34-42g / 10min;

[0032] An injection molding machine is used to prepare an ASTM notched impact specimen, the specimen thickness is 3.2 mm, the width is 12.7 mm, the length is 63.5 mm, and the pendulum energy is 2.75 J. The notched cantilever beam impact strength is tested according to ASTM D256 at 23° C. The notched cantilever beam impact strength of the PC / ABS composition of the present invention is ≥580 J / m, preferably above 582 J / m, and more preferably 582-610 J / m;

[0033] The load deformation temperature is tested according to ASTM D648-18 method, with a load of 1.82 MPa. The heat deformation temperature of the PC / ABS composition of the present invention is ≥95° C., preferably above 95.4° C.

[0034] The second aspect of the present invention is to provide a method for preparing the PC / ABS composition described in the first aspect, comprising the steps of mixing, extruding, cooling and granulating raw materials including the PC resin, ABS resin, flame retardant, synergistic flame retardant, impact modifier, compatibilizer, anti-drip agent and antioxidant according to a proportion.

[0035] According to the above technical solution of the present invention, the extrusion is carried out in a twin-screw extruder.

[0036] The extrusion conditions can be selected within a wide range. In a preferred embodiment of the present invention, the extrusion temperature is 220-255° C., and / or the screw speed is 200-280 rpm.

[0037] The preparation method of the PC / ABS composition comprises: the PC / ABS composition contains 60 to 80 parts of PC resin and 20 to 40 parts of ABS resin in parts by weight;

[0038] Relative to 100 parts of the total amount of PC resin and ABS resin, the PC / ABS composition further contains:

[0039] Flame retardant 10-18 parts,

[0040] Synergistic flame retardant 0.5-6 parts,

[0041] 5-8 parts of impact modifier,

[0042] Compatibilizer 0.5-2 parts,

[0043] 0.2-0.6 parts of anti-dripping agent,

[0044] 0.2-0.5 parts of antioxidant;

[0045] The flame retardant is a phosphate flame retardant, and the synergistic flame retardant is a halogen-free, environmentally friendly flame retardant masterbatch containing no potassium perfluorobutyl sulfonate and polycarbonate as a carrier.

[0046] According to the present invention, the synergistic flame retardant is a halogen-free, environmentally friendly flame retardant masterbatch without potassium perfluorobutyl sulfonate and with polycarbonate as a carrier. In a preferred embodiment of the present invention, the synergistic flame retardant contains polycarbonate, UASIC silsesquioxane flame retardant, Wacker silicon dispersant AK50 and antioxidant, for example, the synergistic flame retardant purchased from Quansheng Polycarbon Technology Co., Ltd. recorded in the embodiment of the present invention. The present invention selects environmentally friendly and efficient flame retardant masterbatch as the synergistic flame retardant, which can meet the requirements of good compatibility with other parts and uniform distribution of components during the extrusion process; it can also reduce or inhibit the loss of mechanical properties and heat resistance of alloy materials caused by phosphate flame retardants, especially the effect on heat deformation temperature.

[0047] According to the present invention, the melt mass flow rate (i.e., melt index) of the PC resin can be selected within a wide range. In a preferred embodiment of the present invention, under the test conditions of a temperature of 300° C. and a load of 1.2 kg, the melt mass flow rate of the PC resin is 7 to 17 g / 10 min, for example, a melt index of 7 g / 10 min, a melt index of 12 g / 10 min, a melt index of 17 g / 10 min, and any two values ​​or any interval between any two values, preferably 11 to 13 g / 10 min.

[0048] According to the present invention, the rubber content in the ABS resin can be selected within a wide range. In a preferred embodiment of the present invention, based on the total weight of the ABS resin as 100wt%, the rubber content in the ABS resin is 11-13wt%, preferably 12.5-13wt%.

[0049] In a preferred embodiment of the present invention, the impact modifier is a methyl methacrylate-butadiene-styrene terpolymer and / or a silicon-based core-shell copolymer; preferably,

[0050] The model of the methyl methacrylate-butadiene-styrene terpolymer is M-722, and / or the model of the silicon-based core-shell copolymer is S2030.

[0051] In a preferred embodiment of the present invention, the flame retardant is at least one of triphenyl phosphate, bisphenol A bis(diphenyl) phosphate, and hydroquinone bis(diphenyl phosphate).

[0052] In a preferred embodiment of the present invention, the compatibilizer is a non-crystalline copolymer of methyl acrylate, preferably SAG-002, purchased from Jiayirong Polymer (Shanghai) Co., Ltd.

[0053] In a preferred embodiment of the present invention, the anti-dripping agent is a copolymer of polytetrafluoroethylene, preferably K-PT201, purchased from Quansheng Polycarbon Technology Co., Ltd.

[0054] In a preferred embodiment of the present invention, the antioxidant contains a hindered phenol antioxidant and a phosphite, and preferably the mass ratio of the hindered phenol antioxidant to the phosphite is 1:(0.5-1.5).

[0055] In a preferred embodiment of the present invention, the PC / ABS composition contains 65-75 parts of PC resin and 25-35 parts of ABS resin, by weight.

[0056] In a preferred embodiment of the present invention, the PC / ABS composition contains, by weight, 12 to 15 parts of flame retardant, 2 to 3 parts of synergistic flame retardant, 6 to 7 parts of impact modifier, 0.8 to 1 part of compatibilizer, 0.2 to 0.4 part of anti-drip agent, and 0.3 to 0.4 part of antioxidant, relative to 100 parts of the total amount of PC resin and ABS resin.

[0057] The third aspect of the present invention is to provide an application of the PC / ABS composition described in the first aspect or the PC / ABS composition prepared by the preparation method described in the second aspect in automobile parts, office equipment housings, home appliance housings, and communication equipment housings.

[0058] As described in the background of the present invention, phosphate-type flame retardants are often used to prepare halogen-free flame-retardant PC / ABS alloy materials on the market. However, phosphate-type flame retardants have a plasticizing effect, which will cause the impact resistance and heat resistance of the material to decrease a lot, thereby limiting the application of the alloy material. Even if the PC / ABS material in the prior art solves the fluidity problem of the material, the flame retardant performance index cannot meet the application requirements. It is difficult to obtain a PC / ABS material with high impact resistance, high fluidity, high heat resistance and halogen-free flame retardancy in the prior art.

[0059] The invention adopts a specific formula (raw material types and proportions) to provide a novel PC / ABS composition, wherein the PC / ABS composition contains 60-80 parts of PC resin and 20-40 parts of ABS resin in parts by weight; relative to a total of 100 parts of PC resin and ABS resin, the PC / ABS composition further contains: 10-18 parts of flame retardant, 0.5-6 parts of synergistic flame retardant, 5-8 parts of impact modifier, 0.5-2 parts of compatibilizer, 0.2-0.6 parts of anti-dripping agent and 0.2-0.5 parts of antioxidant; wherein the flame retardant is a phosphate flame retardant, and the synergistic flame retardant is a halogen-free environmentally friendly flame retardant masterbatch containing potassium perfluorobutyl sulfonate and having polycarbonate as a carrier. From the overall description of the present invention and the relevant verification of the embodiments, it can be seen that the preparation process of the PC / ABS composition of the present invention is simple and the comprehensive performance is good. The prepared PC / ABS alloy material can achieve the following indicators: UL94V-0 (1.6mm), melt mass flow rate (260°C, 5kg) ≥30g / 10min, notched Izod impact strength (3.2mm) ≥580J / m, heat deformation temperature (1.8MPa) ≥95°C, and can be used to prepare thin-walled and miniaturized consumer electronics and intelligent equipment and other parts to meet market demand.

[0060] In summary, the PC / ABS composition of the present invention has the characteristics of high impact resistance, high fluidity, high heat resistance and halogen-free flame retardancy, and achieves unexpected technical effects. DETAILED DESCRIPTION

[0061] The present invention is described in detail below in conjunction with specific embodiments. It is necessary to point out that the following embodiments are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made to the present invention by those skilled in the art based on the contents of the present invention still fall within the scope of protection of the present invention.

[0062] The present invention will be further described below in conjunction with the embodiments of the present invention:

[0063] The materials used in the embodiments of the present invention and the comparative examples are as follows:

[0064] PC resin, A1: polycarbonate resin with a melt index of 7 g / 10 min, A2: polycarbonate resin with a melt index of 12 g / 10 min, A3: polycarbonate resin with a melt index of 17 g / 10 min, the melt index is tested at a temperature of 300°C and a load of 1.2 kg;

[0065] ABS resin, in terms of weight percentage, B1: acrylonitrile-butadiene-styrene resin with a rubber content of 13 wt%, B2: acrylonitrile-butadiene-styrene resin with a rubber content of 11 wt%;

[0066] Impact modifier, C1: MBS type impact modifier (M-722, Kaneka Chemical, Japan), C2: Silicon-based impact modifier (S2030, Mitsubishi Chemical, Japan);

[0067] Flame retardant, D1: liquid phosphate (bisphenol A bis (diphenyl phosphate) model is WSFR-BDP, Zhejiang Wansheng), D2: solid phosphate (polyaryl phosphate, model is WSFR-PX-220, Zhejiang Wansheng)

[0068] The synergistic flame retardant contains polycarbonate resin, UASIC silsesquioxane, Wacker silicon dispersant AK500, and antioxidant, which are purchased from Quansheng Polycarbonate Technology Co., Ltd.

[0069] The compatibilizer was SAG002, purchased from Jiayirong Polymer (Shanghai) Co., Ltd.;

[0070] The anti-drip agent was K-PT201, purchased from Quansheng Polycarbon Technology Co., Ltd.;

[0071] The model of the antioxidant is 1010,168, the mass ratio is 1:1, and it was purchased from Tianjin Lianlong New Materials Co., Ltd.

[0072] Examples 1 to 6

[0073] According to the ratio in Table 1, PC resin, ABS resin, flame retardant, impact modifier and other additives were added to a high-speed mixer and mixed for 10 minutes according to weight, and then added to a twin-screw extruder for screw extrusion, cooling and granulation. The extruder temperature was controlled at 220-255°C and the screw speed was 200-280rpm.

[0074] The prepared composite particles were dried in a constant temperature forced air drying oven at 90° C. for 2 h, and then injection molded into ASTM specimens using an injection molding machine for flame retardancy, heat resistance and Izod notched impact strength tests.

[0075] Comparative Example 1

[0076] PC resin, ABS resin, flame retardant, impact modifier and other additives are added to a high-speed mixer according to weight proportions and mixed for 10 minutes, then added to a twin-screw extruder for screw extrusion, cooling and granulation. The extruder temperature is controlled at 220-255°C and the screw speed is 200-280rpm.

[0077] Comparative Example 2

[0078] PC resin, ABS resin, flame retardant, potassium perfluorobutyl sulfonate, impact modifier and other additives are added to a high-speed mixer according to weight proportions and mixed for 10 minutes, then added to a twin-screw extruder for screw extrusion, cooling and granulation. The extruder temperature is controlled at 220-255°C and the screw speed is 200-280rpm.

[0079] Comparative Example 3

[0080] The raw material components shown in Table 1 were extruded according to the method of Example 1.

[0081] Comparative Example 4

[0082] The raw material components shown in Table 1 were extruded according to the method of Example 1.

[0083] Test example

[0084] Test methods for various properties

[0085] (1) Izod notched impact strength test

[0086] An injection molding machine was used to prepare ASTM notched impact specimens with a thickness of 3.2 mm, a width of 12.7 mm, a length of 63.5 mm, and a pendulum energy of 2.75 J. The notched cantilever beam impact strength was tested at 23°C according to ASTM D256, and the results were recorded in J / m.

[0087] (2) Melt mass flow rate test

[0088] Tested according to ISO 1133-1:2011 Method A, temperature 260°C, load 5Kg.

[0089] (3) Flame retardant performance test

[0090] Use an injection molding machine to prepare 1.6mm thick specimens. According to the UL94 vertical burning test standard, prepare 5 specimens to test the burning time and afterglow time. The results are expressed as 5VB, 5VA, V-0, V-1, and V-2.

[0091] (4) Heat deformation temperature

[0092] An injection molding machine was used to prepare 6.4 mm thick specimens, and the load deformation temperature was tested according to the ASTM D648-18 method with a load of 1.82 MPa.

[0093] Table 1: Weight parts and performance tests of Examples 1-6 and Comparative Examples 1-4

[0094]

[0095]

[0096] It can be seen from Example 1 and Comparative Example 3 in Table 1 that the flame retardant grade of the PC / ABS alloy material without the addition of the synergistic flame retardant is UL94 (1.6 mm) V1, and the flame retardant grade of the PC / ABS alloy material with the addition of the synergistic flame retardant is UL94 (1.6 mm) V0. Moreover, the properties of the composition in Comparative Example 3, such as the cantilever beam notched impact strength and the heat deformation temperature, are also greatly reduced.

[0097] It can be seen from the examples and comparative example 4 in Table 1 that even if the same raw materials are used, the flame retardant grade of the composition in comparative example 4 obtained without using the ratio in the present invention is UL94 (1.6 mm) V1, which does not reach the UL94 (1.6 mm) V0 grade, the melt mass flow rate is reduced, which affects the processing performance, and the performances such as the Izod notched impact strength and the heat deformation temperature also decrease to varying degrees; the effects of good flame retardancy, high impact strength and high heat deformation temperature cannot be achieved at the same time.

[0098] By comparing Examples 1 and 2 with Comparative Examples 1 and 2, it can be seen that the PC / ABS alloy material without adding synergistic flame retardant has the highest melt mass flow rate and the best processing performance, but under the condition of ensuring that the flame retardant performance of the product meets the standard, the notched impact strength and heat deformation temperature of the material decrease a lot, which limits the application range of the material. Adding potassium perfluorobutyl sulfonate as a synergistic flame retardant has little effect on the mechanical properties of the material, but the heat deformation temperature decreases a lot, and the stability of the material added with potassium perfluorobutyl sulfonate is not good. As time goes on, the flame retardant component will seep out, resulting in a decrease in the flame retardant performance of the material. The present invention uses an environmentally friendly and efficient flame retardant masterbatch that does not contain potassium perfluorobutyl sulfonate as a synergistic flame retardant to prepare a halogen-free flame retardant PC / ABS composition. While ensuring that the flame retardant grade reaches UL94V-0 (1.6mm), it ensures that the mechanical properties and heat resistance of the product are not lost, and the processing performance is good.

[0099] In Examples 1, 2, 3, 4, 5, and 6 of the present invention, by examining the base resin material, using base resins with different properties, different base resin ratios, and adding different amounts of auxiliary components, the prepared PC / ABS alloy materials can achieve the following indicators: UL94V-0 (1.6mm), melt mass flow rate (260°C, 5kg) ≥30g / 10min, notched Izod impact strength (3.2mm) ≥580J / m, heat deformation temperature (1.8MPa) ≥95°C. The obtained PC / ABS composition of the present invention has the characteristics of high impact resistance, high fluidity, high heat resistance and halogen-free flame retardancy. The alloy product can be used to prepare thin-walled and miniaturized consumer electronics and intelligent equipment.

[0100] It should be noted that the embodiments described above are only used to explain the present invention and do not constitute any limitation to the present invention. The present invention has been described with reference to typical embodiments, but it should be understood that the words used therein are descriptive and explanatory words, rather than restrictive words. The present invention may be modified as specified within the scope of the claims of the present invention, and the present invention may be revised without departing from the scope and spirit of the present invention. Although the present invention described therein relates to specific methods, materials and embodiments, it does not mean that the present invention is limited to the specific examples disclosed therein, on the contrary, the present invention can be extended to all other methods and applications with the same functions.

[0101] All publications, patent applications, patents and other references mentioned in this specification are incorporated herein by reference. Unless otherwise defined, all technical and scientific terms used in this specification have the meanings conventionally understood by those skilled in the art. In the event of a conflict, the definition in this specification shall prevail.

[0102] When this specification uses the prefix "well-known to those skilled in the art", "prior art" or similar terms to introduce materials, substances, methods, steps, devices or components, etc., the objects introduced by the prefix cover those commonly used in the art when this application is filed, but also include those that are not commonly used at present but will become recognized in the art as being suitable for similar purposes.

[0103] The endpoints and any values ​​of the scope disclosed in the present application document are not limited to the precise scope or value, and these scopes or values ​​should be understood to include values ​​close to these scopes or values. For numerical ranges, between the endpoint values ​​of each scope, between the endpoint values ​​of each scope and a separate point value, and between separate point values, one or more new numerical ranges can be combined with each other, and these numerical ranges should be considered as specifically disclosed in this article. Hereinafter, in principle, each technical solution can be combined with each other to obtain a new technical solution, which should also be considered as specifically disclosed in this article.

[0104] In the context of the present specification, any matters or items not mentioned are directly applicable to those known in the art without any changes except those explicitly stated.

[0105] Moreover, any embodiment described in this document may be freely combined with one or more other embodiments described in this document, and the technical solutions or technical ideas formed thereby are deemed to be part of the original disclosure or original record of the present invention, and should not be regarded as new content that has not been disclosed or anticipated in this document, unless a person skilled in the art considers that the combination is obviously unreasonable.

Claims

1. A PC / ABS composition, comprising 60 to 80 parts of PC resin and 20 to 40 parts of ABS resin, in parts by weight; Relative to 100 parts of the total amount of PC resin and ABS resin, the PC / ABS composition further contains: Flame retardant 10-18 parts, Synergistic flame retardant 0.5-6 parts, 5-8 parts of impact modifier, Compatibilizer 0.5-2 parts, 0.2-0.6 parts of anti-dripping agent, 0.2-0.5 parts of antioxidant; in, The flame retardant is a phosphate flame retardant, and the synergistic flame retardant is a halogen-free, environmentally friendly flame retardant masterbatch containing no potassium perfluorobutyl sulfonate and taking polycarbonate as a carrier.

2. The PC / ABS composition according to claim 1, characterized in that: The synergistic flame retardant contains polycarbonate, UASIC silsesquioxane flame retardant, Wacker silicon dispersant AK50 and antioxidant.

3. The PC / ABS composition according to claim 1, characterized in that: Under the testing conditions of a temperature of 300° C. and a load of 1.2 kg, the melt mass flow rate of the PC resin is 7 to 17 g / 10 min, preferably 11 to 13 g / 10 min.

4. The PC / ABS composition according to claim 1, characterized in that: Based on the total weight of the ABS resin being 100 wt %, the rubber content in the ABS resin is 11 to 13 wt %, preferably 12.5 to 13 wt %.

5. The PC / ABS composition according to claim 1, characterized in that: The impact modifier is a methyl methacrylate-butadiene-styrene terpolymer and / or a silicon-based core-shell copolymer; preferably, The model of the methyl methacrylate-butadiene-styrene terpolymer is M-722, and / or the model of the silicon-based core-shell copolymer is S2030.

6. The PC / ABS composition according to claim 1, characterized in that: The flame retardant is at least one of triphenyl phosphate, bisphenol A bis(diphenyl) phosphate, and hydroquinone bis(diphenyl phosphate).

7. The PC / ABS composition according to claim 1, characterized in that: The compatibilizer is a non-crystalline copolymer of methyl acrylate, preferably SAG-002; and / or, The anti-dripping agent is a copolymer of polytetrafluoroethylene, preferably K-PT201; and / or, The antioxidant contains a hindered phenol antioxidant and a phosphite, and preferably the mass ratio of the hindered phenol antioxidant to the phosphite is 1:(0.5-1.5).

8. The PC / ABS composition according to any one of claims 1 to 7, characterized in that: In parts by weight, the PC / ABS composition contains 65 to 75 parts of PC resin and 25 to 35 parts of ABS resin; and / or, In parts by weight, relative to 100 parts of the total amount of PC resin and ABS resin, the PC / ABS composition contains: 12 to 15 parts of flame retardant, 2 to 3 parts of synergistic flame retardant, 6 to 7 parts of impact modifier, 0.8 to 1 part of compatibilizer, 0.2 to 0.4 part of anti-drip agent, and 0.3 to 0.4 part of antioxidant.

9. A method for preparing the PC / ABS composition according to any one of claims 1 to 8, comprising: According to the proportion, the raw materials including the PC resin, ABS resin, flame retardant, synergistic flame retardant, impact modifier, compatibilizer, anti-drip agent and antioxidant are mixed, extruded, cooled and granulated; preferably, The extrusion is carried out in a twin-screw extruder; more preferably, Extrusion temperature: 220-255°C, and / or, screw speed: 200-280 rpm.

10. Use of the PC / ABS composition according to any one of claims 1 to 8 or the PC / ABS composition prepared by the preparation method according to claim 9 in automobile parts, office equipment housings, home appliance housings, and communication equipment housings.

Citation Information

Patent Citations

  • High-impact heatproof halogen-free flame-retardant PC / ABS alloy material and preparation method thereof

    CN106905683A

  • High-fluidity high-impact-resistant high-temperature-resistant PC / ABS alloy material and preparation method thereof

    CN112080123A